Fibre retention osseous resective surgery: how deep is the infrabony component of the osseous-resected defects? - Gianfranco Carnevale (Blackwell Synergy, 2008)
Background: The Aims of this retrospective study were: (i) to describe the applicability of Fibre Retention Osseous Resective Surgery (FibReORS) to infrabony defects with different radiographic depths and (ii) to identify significant anatomical elements associated with the decision of tooth extraction or application of FibReORS in the context of a treatment approach aimed at pocket elimination. Material and Methods: Baseline radiographs with detectable infrabony defects were collected from 68 periodontal patients. Selected teeth with radiographic evidence of infrabony defects had probing depths (PD) 44mm at revaluation following non-surgical periodontal therapy. Teeth were then surgically treated with FibReORS or extracted on the basis of the decision making of an experienced periodontist and in the context of the overall treatment plan. The total root length and the defect depth were quantified for each selected tooth using radiographic reference points. Results: A total of 324 teeth with infrabony defects were identified. Fifty-three (16%) teeth with a mean radiographic infrabony defect of 8.5 1.7mm (range 6–12 mm) were extracted; 271 (84%) teeth with a mean infrabony defect of 3.0 1.4mm (1–8 mm) were surgically treated, achieving PD 43mm in all sites at 6-month follow-up. Surgically treated teeth showed baseline radiographic infrabony defects 44mm in 86% of the cases. Logistic multilevel modelling indicated that the probability of extraction was influenced by root length (p50.0230) and by the radiographic defect depth (p50.0112). Conclusion: FibReORS is applicable in the treatment of shallow to moderate bony defects and deeper defects associated with longer roots.